2017
DOI: 10.1007/s00535-017-1318-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after treatment for T1 colorectal carcinoma: a multicenter retrospective cohort study of Hiroshima GI Endoscopy Research Group

Abstract: Our findings supported the JSCCR criteria for endoscopically curable T1 CRC. ER for T1 CRC did not worsen the clinical outcomes of patients who required additional surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
61
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 35 publications
2
61
3
Order By: Relevance
“…More recently, in a retrospective multicenter cohort study in Japan, the primary surgery and secondary surgery groups exhibited recurrence rates of 5.5% and 3.8%, respectively, and overall survival rates of 92.4% and 91.5%, respectively. These studies supported the hypothesis that endoscopic resection for T1 CRC did not worsen clinical outcomes for patients who required additional surgical resection (8). Importantly, Overwater et al reported a total of 16 treatment-related complications leading to death within 30 days after treatment; 15 of these complications were related to surgery (9 leakages, 5 cardiovascular, and 1 abscess), and only one complication was related to endoscopy.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…More recently, in a retrospective multicenter cohort study in Japan, the primary surgery and secondary surgery groups exhibited recurrence rates of 5.5% and 3.8%, respectively, and overall survival rates of 92.4% and 91.5%, respectively. These studies supported the hypothesis that endoscopic resection for T1 CRC did not worsen clinical outcomes for patients who required additional surgical resection (8). Importantly, Overwater et al reported a total of 16 treatment-related complications leading to death within 30 days after treatment; 15 of these complications were related to surgery (9 leakages, 5 cardiovascular, and 1 abscess), and only one complication was related to endoscopy.…”
mentioning
confidence: 59%
“…Importantly, Overwater et al reported a total of 16 treatment-related complications leading to death within 30 days after treatment; 15 of these complications were related to surgery (9 leakages, 5 cardiovascular, and 1 abscess), and only one complication was related to endoscopy. Currently, population aging is occurring throughout Japan, and we should consider a patient's age, wishes, performance status, and quality of life, as well as the operative method (8). Therefore, the indication for endoscopic resection for T1 CRC will be expanded to total excisional biopsy, particularly for limited patients (e.g., patients who are elderly, have concomitant disease, or are restricted with respect to operative method or performance status, among other considerations) in the near future (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Japanese report examined T1 CRC patients treated during 1992-2008 and who had ≥5 years of followup (6). Patients who did not meet the curative criteria after endoscopic resection according to the JSCCR guidelines were defined as "non-endoscopically curable" and classified into three groups: endoscopic resection alone, additional surgery after endoscopic resection, and surgical resection alone.…”
mentioning
confidence: 99%